2020
DOI: 10.2139/ssrn.3744427
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification of the Genetic Basis of Amyotrophic Lateral Sclerosis

Abstract: Highlights d Machine learning method identifies risk genes by integrating GWASs and epigenetic data d Discovered ALS risk genes lead to a 5-fold increase in recovered heritability d Genetic and experimental support for initiation of ALS pathogenesis in the distal axon d Convergent genetic and experimental data establish KANK1 as a new ALS gene

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 88 publications
0
8
0
Order By: Relevance
“…Vesicle mediated transport is involved in synaptic neurotransmission but also in vesicle fusion, which is an essential component of autophagy ( 57 ). Our study of the genetic architecture of ALS in the context of motor neuron function highlighted function within the distal axon ( 17 ) and demonstrated that axonal dysfunction associated with LoF of KANK1 , a putative new ALS gene, may be upstream of TDP-43 mislocalization.…”
Section: Als Risk Genes Converge In Pathwaysmentioning
confidence: 85%
See 1 more Smart Citation
“…Vesicle mediated transport is involved in synaptic neurotransmission but also in vesicle fusion, which is an essential component of autophagy ( 57 ). Our study of the genetic architecture of ALS in the context of motor neuron function highlighted function within the distal axon ( 17 ) and demonstrated that axonal dysfunction associated with LoF of KANK1 , a putative new ALS gene, may be upstream of TDP-43 mislocalization.…”
Section: Als Risk Genes Converge In Pathwaysmentioning
confidence: 85%
“…Both regulatory and coding variants within the NEK1 and TBK1 loci are thought to cause loss of function (LoF) of the target gene in ALS patients. Similarly we have profiled ALS-associated regulatory variation and identified other non-GWAS hits where there is a convergence of common and rare variant signal in a LoF mechanism ( 5 , 17 ). Moreover, a similar phenomenon has been reported in other disease areas ( 30 ).…”
Section: Impact Of New Gwasmentioning
confidence: 99%
“…Whole genome sequencing and clinical data of ALS cases from Project MinE (data freeze 2) were used for the survival and age of onset analyses (29,30). Samples were filtered to remove common variants (MAF > 0.01) in the enhancer regions of CAV1 and CAV2 genes, which are defined in Cooper-Knock et al, 2020 (17).…”
Section: Methodsmentioning
confidence: 99%
“…Project MinE is at the forefront of these approaches, with efforts to sequence the genome and connect findings with transcriptome, epigenome, and noncoding genome findings. 55,56 Other data sets are also taking integrative approaches and providing resources for researchers at large for straightforward access to sample data. The Answer ALS consortium is one such approach, which provides whole genome data along with induced pluripotent stem cell lines and their corresponding transcriptome data, thereby saving researchers precious time and resources in trying to generate their own version of these lines.…”
Section: Challenges In Als Genetics and Exploring Emerging Solutionsmentioning
confidence: 99%